Solar power feeds twelve - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
A low-cost solar cooker built largely of mud and straw (adobe) has been successfully tested in Tanzania. Costing aboutUS$12, which is one-fifth the cost of other solar cookers, it is considered to be the first truly affordable, yet robust...